ECONOMIC AND ENVIRONMENTAL ASPECTS OF AGRI-FOOD SYSTEM IN THE EU MEMBER STATES AND UKRAINE IN CONTEXT OF THE EUROPEAN GREEN DEAL OBJECTIVES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The main objective of the European Green Deal is to achieve full climate neutrality of the EU by 2050, including the agri-food system, which occupies a prominent place in the community economy. Producing zero net greenhouse gas emissions and promoting the sustainable development of the sector in the long term means a green transformation of all components of the EU agri-food system, primarily agricultural production and food industry. It has been determined that agricultural production is one of the main GHG emitters in the agri-food system of the EU and Ukraine, ahead of the food and processing industry. It has also been revealed that the amount of GHG (in carbon dioxide equivalent) from agricultural production per one US dollar of value added significantly exceeds the same value from the food and processing industry. This proves the fact that production of finished food is more sustainable than production of agricultural raw materials. Thus, progress in addressing the issue of achieving climate neutrality and ensuring sustainable development of the EU agri-food system largely depends on the greening of agriculture and the deepening of the degree of processing of agricultural raw materials. It is substantiated that in the context of Ukraine's integration into the EU, it is advisable to pay significant attention to the development of its own food and processing industry, which is not only beneficial from an economic side, but should also contribute to better achieving the European Green Deal purpose. It was clarified that in Ukraine and the EU, household food consumption and food waste disposal account for a relatively high percentage of GHG in the structure of the agri-food system. The study is based on 2022 data.